Ta‘zīz Mahārat al-Kalām bi-Istikhdām Ādat Voicemaker al-Mu‘tamidah ‘alā Tiqniyāt al-Dhakā’ al-Iṣṭinā‘ī: Dirāsat Ḥālah ‘alā Ṭullāb al-Mustawā al-Ibtida‘ī - Wiwik Prasetiyo Ningsih; Jiddah Hassan Muhammad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study explores the use of Artificial Intelligence technology, specifically Voicemaker applications, in improving speaking skills. The aims of this study are identifying the steps for using Voicemaker and identifying the challenges and solutions in utilizing AI Voicemaker during the teaching and learning speaking skills process. The research employs a qualitative approach using a case study method. Data were collected through interviews, documentation, and observations of participants engaging with the technology in various learning contexts. The data were analyzed using thematic analysis. Findings indicate that the use of AI Voicemaker in teaching Arabic speaking skills is carried out through six steps: sound presentation by AI as auditory input, pronunciation imitation by students, structured practice (question and answer, substitution, transformation), free practice through dialogue and simulation, reinforcement with audio-visual media, and pronunciation evaluation and correction. In its implementation, the use of AI Voicemaker in teaching Arabic speaking skills to beginner-level students faces several challenges, including difficulties in imitating complex Arabic phonemes such as ‘ain and ghain, the lack of interactivity in providing feedback, students’ low self-awareness of pronunciation errors, and boredom caused by passive listening activities. The applied solutions include phonetic guidance from the teacher, the use of peer correction, self-monitoring exercises, and varied methods to make learning more interactive and contextual. The contribution of this research lies in providing a practical model for integrating AI-based Voicemaker tools into Arabic speaking instruction, offering structured steps and adaptive solutions that can guide educators in developing more effective, interactive, and technology-supported language learning environments.